COVID-19: Utilizing local experience to suggest optimal global strategies to prevent and control the pandemic - Mahmud, Ilias; Al-Mohaimeed, Abdulrahman (International Journal of Health Sciences, 2020)
In December 2019, an outbreak of Coronavirus Disease 2019 (COVID-19), an acute respiratory illness caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), was detected in Wuhan, China. On 11 March 2020, the World Health Organization (WHO) declared COVID-19 a pandemic and advised all countries to take decisive actions to prevent and control the outbreak. Thus far, as of 16 April 2020, COVID-19 has spread to 213 countries or territories and resulted in 1,954,724 confirmed cases and 126,140 deaths globally. There is no effective vaccine to prevent COVID-19, and treatment options are still experimental and unproven. Patients are just managed with supportive care and antibiotics against secondary bacterial infections. To fight this pandemic, many high-income countries, including Saudi Arabia, locked their borders, started evacuating their citizens from other countries and imposed different degrees of blockade locally to promote social distancing and, hence, controlling the spread of the virus, SARS-CoV-2. In this editorial, we will discuss the adequacy of such measures to control COVID-19 epidemic locally and globally.